Indicadores para a formação de pedagogos na educação a distância - Leal, Marcello Guimarães (2012)
The integral formation of the educationalist, particularly in Distance Education (DE), requires discussion among educators and trainers of teachers, and constitutes our research problem, namely: what are the key indicators in the process of formation of educators in distance learning courses and how they become present in the curriculum activities contained in pedagogic project of the course and in the conception of managers and teachers? To answer this question, the goal is: (1) identify and describe indicators for training of educators in DE, from the current legislation; (2) analyze the indicators for the formation of the teacher, from the Pedagogical Political Project proposed in a course of pedagogy in DE of a public university; (3) check the conception of managers and teachers with regard to the indicators for the formation of the pedagogue in DE; (4) submit contributions to possible improvements in teacher training in the proposal of DE. The study is delimited based on a survey held in a public Higher Education Institution (HEI) linked to Open University of Brazil (OUB), and to the proposal on distance education for public school teachers, in 80 of the vacancies, being 20 aimed at people seeking pedagogical training. The establishment of indicators for the formation of the pedagogue in Distance Education is made from: National Curriculum Guidelines of the Pedagogic Course; Brazilian Legislation for Distance Education; from the document of the National Conference of Education for the training of teachers in Distance Education and from the Quality Benchmarks proposed by the OUB. Based on these indicators, it is conducted an exploratory study based on the analysis of Pedagogical Political Project of the Course of Pedagogy in DE and the conception of managers and teachers of this course. In the study, 04 managers and 08 professors of Pedagogy in DE participated, being contacted from 2011 to 2012. The importance of discussing and highlighting indicators of formation of pedagogue in the DE is to contribute to the improvement of teacher training in this modality, in courses that are throughout the country, in addition to offering subsidies to think of teaching alternatives to learning and to the integral formation of the professional in the area of education. The survey results pointed to strengths and to the improving in relation to teacher training in distance learning course, and found the need to (re)think continually the curriculum and the educational curricular proposals, from the specifics of training in DE, seeking the improvement of teacher training in remote mode